2003
DOI: 10.1016/s0012-1606(02)00099-4
|View full text |Cite
|
Sign up to set email alerts
|

EIF4E/4E-BP dissociation and 4E-BP degradation in the first mitotic division of the sea urchin embryo

Abstract: The mRNA's cap-binding protein eukaryotic translation initiation factor (eIF)4E is a major target for the regulation of translation initiation. eIF4E activity is controlled by a family of translation inhibitors, the eIF4E-binding proteins (4E-BPs). We have previously shown that a rapid dissociation of 4E-BP from eIF4E is related with the dramatic rise in protein synthesis that occurs following sea urchin fertilization. Here, we demonstrate that 4E-BP is destroyed shortly following fertilization and that 4E-BP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 47 publications
11
52
0
3
Order By: Relevance
“…Consistent with this, phosphorylation correlates with a dramatic loss of the protein following the fertilization of sea urchin eggs (Cormier et al, 2001;Salau¨n et al, 2003), and rapamycin has an inhibitory effect on the loss of 4E-BP in this system. In contrast, in adipocytes insulin (which stimulates the phosphorylation of 4E-BP1) has been reported to increase the halflife of the protein .…”
Section: Phosphorylation Ubiquitination and Stability Of 4e-bp1supporting
confidence: 64%
See 1 more Smart Citation
“…Consistent with this, phosphorylation correlates with a dramatic loss of the protein following the fertilization of sea urchin eggs (Cormier et al, 2001;Salau¨n et al, 2003), and rapamycin has an inhibitory effect on the loss of 4E-BP in this system. In contrast, in adipocytes insulin (which stimulates the phosphorylation of 4E-BP1) has been reported to increase the halflife of the protein .…”
Section: Phosphorylation Ubiquitination and Stability Of 4e-bp1supporting
confidence: 64%
“…Following fertilization of sea urchin eggs, there is a rapid loss of 4E-BP which occurs in parallel with dramatically enhanced rates of protein synthesis (Cormier et al, 2001;Salau¨n et al, 2003). This loss is inhibited by rapamycin, suggesting a role for protein phosphorylation in the degradation of 4E-BP.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Cormier et al demonstrated that the dissociation of eIF4E from 4E-BP and subsequent degradation of 4E-BP, following fertilization of sea urchin eggs, led to an increase in capdependent translation. This is critical for the first mitotic division of sea urchin embryos (Cormier et al, 2001;Salaun et al, 2003). eIF4E and apoptosis eIF4E also mediates cell survival and apoptosis (reviewed in Clemens 2001;Dua et al , 2001).…”
Section: Eif4e and Embryogenesis/reproductionmentioning
confidence: 99%
“…For example, following fertilization of sea urchin eggs, 4E-BP1 is rapidly degraded, and this coincides with an increase in the rate of protein synthesis during early embryogenesis in this system. 119 Conversely, the level of 4E-BP1 increases rapidly and substantially when either human lymphoma or breast cancer cell lines are treated with TRAIL (I Jeffrey, A Elia and MJ Clemens, unpublished data). We do not yet know the mechanism of the TRAIL-mediated accumulation of 4E-BP1.…”
Section: E-bp1mentioning
confidence: 99%